Influence Of Squeegee Impact On Stencil Printing Process- CFD Approach - Samad, Mohd Hazim Sadiq Abd (Universiti Sains Malaysia, 2017)
High requirement of smaller size, lighter weight, and high performance PCB in electronic packaging has contributed to the wide application of stencil printing for soldering process. Stencil printing offers good consistency of soldering performance as well as produce larger process output at short time that make it one of the best option for high volume application in Surface Mount Technology (SMT). However, the soldering method also contributes to major percentage of soldering defect compared to other methods which is necessary to be addressed through research and development. One of the common defects due to the stencil printing is regarding to the printing quality of solder paste on substrate such as Printed Board Circuit (PCB) with respect to the variation of process parameters. Uncontrolled process parameters cause the soldering defects such as solder bridging that can lead to product failure in further processes in production line. An investigation has been conducted to predict the real time observation of solder paste Sn96.5Ag3.0Cu0.5 (SAC305) filling process into stencil apertures as well as print quality in stencil printing by using Computational Fluid Dynamics (CFD) approach. A 3-Dimensional stencil printing model was developed and simulated in FLUENT by using different squeegee parameters which are angle and print speed. An experimental work was performed to be compared with part of the simulation results in term of print quality for validation purpose. It is found that squeegee angle 60° to 80° has potential to obtain good print quality of solder paste. In addition, print speed range between 35 mm/s to 95 mm/s also can be the good print speed option to achieve good print quality in stencil printing process. Finally, the maximum pressure distribution of solder paste also changes substantially as the squeegee travel further with respect to different values of tested parameters.